2014
DOI: 10.15517/rbt.v62i2.9853
|View full text |Cite
|
Sign up to set email alerts
|

Dieta y disponibilidad de forraje del venado cola blanca Odocoileus virginianus thomasi (Artiodactyla: Cervidae) en un campo experimental de Campeche, México

Abstract: Forage use and availability for white tailed deer Odocoileus virginianus thomasi (Artiodactyla: Cervidae) in an experimental unit of Campeche, Mexico. In Campeche state, 122 Wildlife Conservation and Management Units have been recently conformed. In these units, eventhough the white tailed deer Odocoileus virginianus thomasi is a game species, no studies on its diet have been undertaken. The objectives of this work were to estimate the botanical composition of the diet and its seasonal change, to determine for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…In the study site, the white-tailed deer consume a small proportion of Mimosa polyantha during the dry season [42]. This foraging pattern has also been reported in other regions [43].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the study site, the white-tailed deer consume a small proportion of Mimosa polyantha during the dry season [42]. This foraging pattern has also been reported in other regions [43].…”
Section: Discussionsupporting
confidence: 59%
“…The TDF dominated by Neobuxbaumia, Bursera and Mimosa is therefore the vegetation type that offers better habitat conditions and important food resources for the white-tailed deer in this location [43, 45, 46]. In a previous study in four locations of the Tehuacán-Cuicatlán Biosphere Reserve, including San Gabriel Casa Blanca, the variables associated with white-tailed deer density were: basal area, distances to roads and to the area with largest human population, slope, aspect, and presence of cattle [23].…”
Section: Discussionmentioning
confidence: 99%
“…For the Mixteca region of Puebla, Villarreal-Espino (2006) reports 133 species grouped in 50 botanical families, but once again only a few contributed to the largest percentage. Granados-Rivera et al (2014) report 40 species of 15 families in a study done in Campeche. In general, the white tailed deer selected a high number tendencia marginalmente significativa (P = 0.051) de mayor consumo de ramas y hojas en comparación con el BTS.…”
Section: Resultados Y Discusiónmentioning
confidence: 99%
“…Food habit studies of white tailed deer have been carried out in Mexico, in pine-oak temperate forests (AguileraReyes et al, 2013;Gallina, Maury, & Serrano, 1981;González & Briones-Salas, 2012), in xeric shrublands of the northeast (Martínez, Molina, González, Marroquín, & Navar, 1997;Ramírez-Lozano, 2004) and in tropical regions (Arceo, Mandujano, Gallina, & Pérez, 2005;Granados-Rivera et al, 2014;López-Pérez, Serrano, Aguilar, & Herrera, 2012;Plata et al, 2009). The white tailed deer inhabits the Tehuacán-Cuicatlán Biosphere Reserve (RBTC) (Ortiz-García, Ramos-Robles, Pérez-Solano, & Mandujano, 2012) where there is a particular interest in sustainably making use of it in extensive UMAs.…”
Section: Introductionmentioning
confidence: 99%
“…Forage quality and quantity for deer in the Campeche area had significant variations throughout the year in response to the seasonality of the region, with a drastic reduction in the available forage during the dry season compared with the rainy season (Granados et al, 2014). We found that home-range size and core area size were similar throughout the year for the studied females, even during the fawning months (February to June; Contreras-Moreno, Hidalgo-Mihart, Jesús-de la Cruz et al, 2019), when the forage availability was reduced.…”
Section: Discussionmentioning
confidence: 99%